2011
DOI: 10.1016/j.ypmed.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Does a smoking prevention program in elementary schools prepare children for secondary school?

Abstract: A prevention program in elementary school seems to be effective in preventing smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…There is growing evidence indicating that physical activity is important for optimal cognitive and behavioral functioning in children (e.g., Budde, Voelcker-Rehage, PietraByk-Kendziorra, Ribeiro, & Tidow, 2008; Davis et al, 2007; Diamond & Lee, 2011; Diamond, 2013; Tomporowski, Miller, Davis, Miller, & Naglieri, 2008; Tomporowski, Lambourne, & Okumura, 2011). Lakes and Hoyt (2004) demonstrated that a Taekwondo intervention promoted self-regulatory abilities (based on ratings from research observers and teachers) and executive function (based on performance on an executive function task) in school-age children.…”
Section: Self-regulation and Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence indicating that physical activity is important for optimal cognitive and behavioral functioning in children (e.g., Budde, Voelcker-Rehage, PietraByk-Kendziorra, Ribeiro, & Tidow, 2008; Davis et al, 2007; Diamond & Lee, 2011; Diamond, 2013; Tomporowski, Miller, Davis, Miller, & Naglieri, 2008; Tomporowski, Lambourne, & Okumura, 2011). Lakes and Hoyt (2004) demonstrated that a Taekwondo intervention promoted self-regulatory abilities (based on ratings from research observers and teachers) and executive function (based on performance on an executive function task) in school-age children.…”
Section: Self-regulation and Physical Activitymentioning
confidence: 99%
“…Lakes and Hoyt (2004) demonstrated that a Taekwondo intervention promoted self-regulatory abilities (based on ratings from research observers and teachers) and executive function (based on performance on an executive function task) in school-age children. Tomporowski et al (2011) reviewed several exercise interventions with children and concluded that there is compelling evidence suggesting that physical activity benefits children’s cognitive functioning. They noted that that while there are surprisingly few studies examining the impact of physical activity on cognitive functioning, the growth in this field in the last decade has been noteworthy.…”
Section: Self-regulation and Physical Activitymentioning
confidence: 99%
“…Following Botvin's classification (2000), most interventions were based on a social influence approach (e.g. Unplugged program, Caria et al 2011;Crone et al 2011;de Vries et al 2006;Faggiano et al 2008a;Faggiano et al 2010;Koumi and Tsiantis 2001;La Torre et al 2010). They showed some promising effects in the reduction of smoking and alcohol use among youth.…”
Section: Introductionmentioning
confidence: 99%
“…Although smoking levels among primary school pupils are low, this percentage increases rapidly (21% at age 15) when children make the transition to secondary school [3]. Smoking prevention programmes implemented in primary schools have the potential to be effective in preventing the uptake of smoking when children make the transition from primary to secondary school [4]. Since addiction can already occur after smoking only a few cigarettes [5,6], there is a need for smoking prevention programmes targeting primary school children [7].…”
Section: Introductionmentioning
confidence: 99%